2022
DOI: 10.1002/mgg3.1874
|View full text |Cite
|
Sign up to set email alerts
|

De novo DYNC1H1 mutation causes infantile developmental and epileptic encephalopathy with brain malformations

Abstract: Background:The human dynein cytoplasmic 1 heavy chain 1 (DYNC1H1) gene encodes a large subunit of the cytoplasmic dynein complex. DYNC1H1 mutations are associated with various neurological diseases involving both the peripheral and central nervous systems. Methods: The clinical characteristics and genetic data of an infant carrying the de novo DYNC1H1 variant identified by trio exome sequencing were analyzed. Patients with epilepsy with DYNC1H1 mutations were summarized by reviewing the literature. Results: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Furthermore, Hoang et al found that the mutations with the strongest effects on dynein motility were associated with MCD in humans ( 56 ). The mutation detected in our patient (p.Arg292Trp) was previously reported by Benson et al ( 43 ), and a previous study reported that a female with this mutation had focal epilepsy (with onset between 13–18 months) and intellectual disability. A similar phenotype was observed in our patient in that she had early-onset epilepsy and severe intellectual disability.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Hoang et al found that the mutations with the strongest effects on dynein motility were associated with MCD in humans ( 56 ). The mutation detected in our patient (p.Arg292Trp) was previously reported by Benson et al ( 43 ), and a previous study reported that a female with this mutation had focal epilepsy (with onset between 13–18 months) and intellectual disability. A similar phenotype was observed in our patient in that she had early-onset epilepsy and severe intellectual disability.…”
Section: Discussionsupporting
confidence: 84%